2017
DOI: 10.1186/s12864-017-3908-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the aldehyde dehydrogenase gene superfamily in soybean and its potential role in drought stress response

Abstract: BackgroundAldehyde dehydrogenases (ALDHs) represent a group of enzymes that detoxify aldehydes by facilitating their oxidation to carboxylic acids, and have been shown to play roles in plant response to abiotic stresses. However, the comprehensive analysis of ALDH superfamily in soybean (Glycine max) has been limited.ResultsIn present study, a total of 53 GmALDHs were identified in soybean, and grouped into 10 ALDH families according to the ALDH Gene Nomenclature Committee and phylogenetic analysis. These grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 86 publications
(138 reference statements)
5
46
0
Order By: Relevance
“…This SNP is located near Glyma.02g034000, which has an aldehyde dehydrogenase annotation (Table S2). Aldehyde dehydrogenase genes have been previously shown to play a role in response to abiotic stresses of soybeans, and can be highly induced by drought stress in soybean leaves (Wang et al 2017). Loci 12 (Glyma.07g110100) and 33 (Glyma.17g118400) have gene models which encodes a RING superfamily protein (Table S2), and locus 33 was co-located with previously identified canopy wilting QTL.…”
Section: Comparisons Of Genetic Mapping For Canopy Wilting To Previoumentioning
confidence: 84%
“…This SNP is located near Glyma.02g034000, which has an aldehyde dehydrogenase annotation (Table S2). Aldehyde dehydrogenase genes have been previously shown to play a role in response to abiotic stresses of soybeans, and can be highly induced by drought stress in soybean leaves (Wang et al 2017). Loci 12 (Glyma.07g110100) and 33 (Glyma.17g118400) have gene models which encodes a RING superfamily protein (Table S2), and locus 33 was co-located with previously identified canopy wilting QTL.…”
Section: Comparisons Of Genetic Mapping For Canopy Wilting To Previoumentioning
confidence: 84%
“…However, the number of UBC genes in Arabidopsis , rice, tomato, maize, papaya, and longan is 48, 48, 52, 75, 34 and 36, and not correlated with the genome size [ 8 , 16 , 39 , 40 , 41 ]. Several studies have shown that segmental duplications are largely responsible for the expansion of gene families in other plants, such as maize, pineapple and soybean [ 8 , 42 , 43 ]. Unfortunately, there is a lack of information on the chromosomes of longan, therefore we were unable to perform segmental and tandem duplication analysis of DlUBCs .…”
Section: Discussionmentioning
confidence: 99%
“…The cis-elements play an essential role in transcriptional regulation of the gene expression [40]. In this study, the 2000-bp upstream sequences of the identified GmGRAS genes were extracted from the soybean genome, and the cis-element analysis was carried out by using PlantCARE (http://bioinformatics.psb.ugent.be/webtools/plantcare/ html/) (Additional file 10: Table S9).…”
Section: Cis-element Analyses Of Soybean Gmgras Genesmentioning
confidence: 99%